Enhancing History Learning Effectiveness through Teacher Pedagogical Strategies - Fatma Fatma; Idrus Rore; Haliadi Haliadi; Juraid Abdul Latief; Hasan Hasan; Iskandar Ahmad (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The effectiveness of history learning is strongly influenced by teachers' pedagogical strategies in creating meaningful, interactive, and student-centered learning experiences. However, history instruction in many Indonesian secondary schools continues to face challenges related to teacher-centered practices, limited student participation, and insufficient classroom engagement. This study aims to analyze teachers’ pedagogical strategies in enhancing the effectiveness of history learning at SMA Negeri 1 Parigi Tengah, Indonesia. The study employed a qualitative case study design involving history teachers, students, and school administrators selected through purposive sampling. Data were collected through semi-structured interviews, non-participant observations, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings indicate that effective history learning is achieved through the integration of classroom discussion, contextual learning, collaborative activities, questioning techniques, multimedia resources, and reflective learning. These pedagogical strategies foster active student engagement, strengthen historical understanding, improve communication skills, and encourage critical interpretation of historical events. The study further reveals that instructional effectiveness is reinforced by institutional support, including instructional leadership, collaborative professional culture, and systematic instructional planning. This study contributes to history education by conceptualizing teacher pedagogical strategies as an integrated pedagogical ecosystem rather than isolated instructional methods. The findings provide theoretical insights into effective history learning and offer practical recommendations for teachers and school leaders in implementing student-centered pedagogy within the context of the Merdeka Curriculum